Quantitative Trait Locus Mapping and Candidate Gene Analysis for Verticillium Wilt Resistance Using Gossypium barbadense Chromosomal Segment Introgressed Line - Zhao, Jun; Liu, Jianguang; Xu, Jianwen; Zhao, Liang; Wu, Qiaojuan; Xiao, Songhua (Frontiers in Plant Science, 2018)
Verticillium wilt (VW) is a soil-borne fungal disease that is caused by Verticillium dahliae Kleb and seriously damages cotton production annually in China. To date, many efforts have been made to improve the resistance of upland cotton against VW, but little progress has been achieved because of a lack of resistant upland cotton to VW. G. barbadense is known to carry high resistance to VW; however, it is difficult to transfer the resistance trait from G. barbadense to upland cotton because of linkage drag and distortion in the interspecific hybrid. In this study, a chromosomal segment introgression line (CSIL), SuVR043, containing a single and homozygous chromosome segment of G. barbadense cv. H7124 D04 (Chr 22), was created and used to construct an F2 population for mapping of VW resistance quantitative trait loci (QTLs) in the greenhouse. Two major resistance QTLs against nondefoliating V. dahliae isolate Bp2, called qVW-Bp2-1 and qVW-Bp2-2, which were flanked by the markers cgr6409-ZHX37 and ZHX57-ZHX70 and explained an average of 16.38 % and 22.36 % of the observed phenotypic variation, respectively, were detected in three independent replicate experiments. The genetic distances from cgr6409 to ZHX37 and from ZHX57 to ZHX70 were 2.4 cM and 0.8 cM, respectively. By analyzing the genome sequence of the qVW-Bp2-1 and qVW-Bp2-2 regions, we determined that the accurate physical distances from cgr6409 to ZHX37 and from ZHX57 to ZHX70 in the G. barbadense genome are 254 kb and 140 kb, and that those spans 36 and 20 putative genes, respectively. The results of the expression analysis showed significant differences in the expression profiles of GbCYP450, GbTMEM214 and GbRLK among G. barbadense cv. H7124, CSIL SuVR043 and G. hirsutum acc. Sumian 8 at different times after inoculation with V. dahliae isolate Bp2. Virus-induced gene silencing (VIGS) analysis showed that silencing of GbCYP450 and GbTMEM214 decreased H7124 and CSIL SuVR043 resistance to VW. These results form a solid foundation for fine mapping and cloning of resistance genes in the substituted segment and will provide valuable assistance in future efforts to breed for VW resistance.